Pengaruh Store Atmosphere terhadap Minat Beli Konsumen pada Rumah Makan Hawaii, Sanggau Kalimantan Barat - Fernando, Fernando; Djunaid, Ika Suryono (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
Store Atmosphere plays a highly persuasive role in attracting customers and creating a comfortable ambiance within restaurants. The store atmosphere encompasses various elements, including the exterior, general interior, store layout, and interior point of purchase display. The primary objective of this research is to explore the impact of store atmosphere on consumer purchasing interest at Hawaii restaurants, while also reinforcing existing theories. To conduct this study, a sample of 100 responses was collected, and data was gathered using questionnaires and the Likert scale. Several statistical tests, such as validity, reliability, normality, and heteroscedasticity, were employed for data analysis. The information verification approach involved utilizing the basic straight relapse check technique, followed by hypothesis testing using specific t-tests, f-tests, the coefficient of determination (R2) test, and correlation coefficient analysis. Based on the t-test results, it was found that the exterior, general interior, and store layout significantly influence consumer buying interest in Hawaii restaurants. However, the t-test indicated that the interior point of purchase display does not have a significant effect on consumer buying interest in Hawaii restaurants, specifically in Sanggau, West Kalimantan. Additionally, the f-test revealed that both store atmosphere variables and indicators collectively impact consumer buying interest. Furthermore, the coefficient of determination test demonstrated that the R square value is 92.5%. This implies a strong relationship between Store Atmosphere and buyers' purchasing interest, accounting for 92.5% of the variation in the dependent variable. The remaining 7.5% is influenced by various factors not explored in this study. Keywords: Store Atmosphere, Hawaii restaurants, Consumer Buying Interest.